A novel inorganic mesoporous material with a nematic structure derived from nanocrystalline cellulose as the stationary phase for high-performance liquid chromatography. Issue 8 (23rd March 2015) - Zhang, Jun-Hui; Zhang, Mei; Xie, Sheng-Ming; He, Pin-Gang; Yuan, Li-Ming
Abstract : Chiral nematic mesoporous silica (CNMS) was first used as the stationary phase for high-performance liquid chromatographic (HPLC) separation of positional isomers with excellent selectivity. Abstract : Chiral nematic mesoporous silica (CNMS) is a novel inorganic mesoporous material that has properties of both mesoporous and liquid crystal materials. In this work, we report CNMS as a stationary phase for high-performance liquid chromatographic (HPLC) separation of positional isomers. High-resolution separation of aminophenol, dihydroxybenzene, nitroaniline, nitrophenol, chloroaniline, bromoaniline, iodoaniline, dinitrobenzene, nitrochlorobenzene and nitrobromobenzene isomers on CNMS columns was performed. Slurry-packed CNMS columns had better selectivity than commercial β-cyclodextrin HPLC columns for separating these positional isomers. The effects of mobile phase composition, injected analyte mass and column temperature on separation were investigated. The relative standard deviations for five replicate separations of positional isomers were 0.10–0.43% for the retention time and 0.5–3.9% for the peak area. Therefore, CNMS columns are promising for separating positional isomers based on their good reproducibility, high resolution and excellent selectivity. In addition, the column also exhibits recognition ability toward racemates.